On the fractional model of Fokker-Planck equations with two different operator - Korpinar, Zeliha; İnç, Mustafa; Baleanu, Dumitru (Amer Inst Mathematical Sciences-Aims, 2020)
In this paper, the fractional model of Fokker-Planck equations are solved by using Laplace homotopy analysis method (LHAM). LHAM is expressed with a combining of Laplace transform and homotopy methods to obtain a new analytical series solutions of the fractional partial differential equations (FPDEs) in the Caputo-Fabrizio and Liouville-Caputo sense. Here obtained solutions are compared with exact solutions of these equations. The suitability of the method is removed from the plotted graphs. The obtained consequens explain that technique is a power and efficient process in investigation of solutions for fractional model of Fokker-Planck equations.
Keywords: Laplace homotopy analysis method; fractional model of Fokker-Planck equations; Caputo-Fabrizio derivative; series solution